Metal Ecotoxicology concepts & application - Newman, Michael C | McIntosh, Alan W (Lewis Publisher / Orlando, 1991)
Metal ectotoxicology: concepts and applications provides an in depth discussion of varios aspects of metal ecotoxicology state of the art information and techniques in areas rangin from meta behavior in surface waters to bioaccumlation kinetics and toxicoknetics to community effects are presented in a hierarchical arrangement